Low-power and cost-effective readout circuit design for compact semiconductor gas sensor systems - Soon-Kyu Kwon; Jun-Nyeong Kim; Hyung-Gi Byun; Hyeon-June Kim (Electrochemistry Communications, 2024)
This study introduces a novel readout circuit architecture that enhances semiconductor gas sensor systems by reducing power consumption, enabling miniaturization, and improving economic viability. Validated at the PCB level, the design shows strong commercial potential by addressing power efficiency and signal accuracy challenges. The technology is adaptable for applications in environmental monitoring, industrial safety, and medical diagnostics, where efficient and reliable gas sensing is essential.